Undergraduate paediatric teaching-the medical students’ perspective: using the Dundee ready education environment measure questionnaire - Xavier, Rose; Abraham, Bobby; Cherian, Vinod J. (International Journal of Contemporary Pediatrics, 2016)
Background: Educational climate plays a major role in deciding the accomplishment and contentment of the students. Periodic assessment of the educational environment is necessary, after a change in the curriculum and formation of a new exclusive university health care. The objective of the study was to identify the perceptions of medical students undertaking the restructured paediatric curriculum under the newly formed health care university. Methods: After taking required consents, the Undergraduate paediatric teaching-the medical students’ perspective: using the Dundee ready education environment measure questionnaire (DREEM) questionnaire was administered to medical students in all the three medical colleges in Thrissur, in a face to face session and the data analysed. Results: The overall average score was 122.21±21.18 on 200 with final year students giving a significantly higher score as compared to pre-finals (p=0.0001). Female students gave a more positive score as compared to male students (p=0.0083). The items that scored below 2 out of a maximum score of 4 are “Teaching over emphasizes factual learning (1.71±0.81), Teachers are authoritarian (1.62±0.87), I am able to memorize all I need (1.54±1.04), There is a good support system for students who get stressed (1.76±1.02) and I am rarely bored on this course (1.95±1.12)”. Highest score was given by final year medical students for “teachers’ are knowledgeable” (3.48±0.59). Conclusions: Paediatric education should emphasise on problem based learning. Teachers should have regular faculty development programme. Small groups of students need to be assigned to counsellors and mentors, who can be faculty members. Regular feedback needs to be taken from students to make them partners in education rather than as only receivers.